Retinoic Acid signalling and the control of meiotic entry in the human fetal gonad. - Andrew J Childs; Gillian Cowan; Hazel L Kinnell; Richard A Anderson; Philippa T K Saunders (PLoS ONE, 2011)
The development of mammalian fetal germ cells along oogenic or spermatogenic fate trajectories is dictated by signals from the surrounding gonadal environment. Germ cells in the fetal testis enter mitotic arrest, whilst those in the fetal ovary undergo sex-specific entry into meiosis, the initiation of which is thought to be mediated by selective exposure of fetal ovarian germ cells to mesonephros-derived retinoic acid (RA). Aspects of this model are hard to reconcile with the spatiotemporal pattern of germ cell differentiation in the human fetal ovary, however. We have therefore examined the expression of components of the RA synthesis, metabolism and signalling pathways, and their downstream effectors and inhibitors in germ cells around the time of the initiation of meiosis in the human fetal gonad. Expression of the three RA-synthesising enzymes, ALDH1A1, 2 and 3 in the fetal ovary and testis was equal to or greater than that in the mesonephros at 8-9 weeks gestation, indicating an intrinsic capacity within the gonad to synthesise RA. Using immunohistochemistry to detect RA receptors RARα, β and RXRα, we find germ cells to be the predominant target of RA signalling in the fetal human ovary, but also reveal widespread receptor nuclear localization indicative of signalling in the testis, suggesting that human fetal testicular germ cells are not efficiently shielded from RA by the action of the RA-metabolising enzyme CYP26B1. Consistent with this, expression of CYP26B1 was greater in the human fetal ovary than testis, although the sexually-dimorphic expression patterns of the germ cell-intrinsic regulators of meiotic initiation, STRA8 and NANOS2, appear conserved. Finally, we demonstrate that RA induces a two-fold increase in STRA8 expression in cultures of human fetal testis, but is not sufficient to cause widespread meiosis-associated gene expression. Together, these data indicate that while local production of RA within the fetal ovary may be important in regulating the onset of meiosis in the human fetal ovary, mechanisms other than CYP26B1-mediated metabolism of RA may exist to inhibit the entry of germ cells into meiosis in the human fetal testis.